STUDENTS’ INVOLVEMENT IN EFL ONLINE CLASSROOM DURING THE COVID-19 PANDEMIC ERA - Nur Isnani Isna (English Education Department, 2021)
One of the government's policies to stop the spread of the covid-19 pandemic is to shift face-to-face learning at school to distance learning at home. Online learning is not easy to do, it is different from conventional learning. In online classes, students were reluctant to participate in the in-class activities. This kind of reluctance made students lose motivation to learn languages. This study aims to see how the online learning model is to find out the students’ involvement in EFL online classes during the Covid-19 Pandemic at Senior High School in Bengkalis. This present study employs a descriptive case study as the research design. To collect the data, researchers used observation, video documentation, and interviews. Meanwhile, the data analysis technique used in this study were used qualitative data analysis techniques which include three activities, namely: data reduction, data presentation, concluding. The results of this study revealed that. Students could not see the screen display, teacher and student communicating to solve problems, there is a network disruption, students late response to teacher, the class leader is the student who always actively responds to the teacher, students do not respond to teacher directions, students sign in and sign out the zoom meeting